2017
DOI: 10.1128/jvi.01995-16
|View full text |Cite
|
Sign up to set email alerts
|

Domain Interaction Studies of Herpes Simplex Virus 1 Tegument Protein UL16 Reveal Its Interaction with Mitochondria

Abstract: The UL16 tegument protein of herpes simplex virus 1 (HSV-1) is conserved among all herpesviruses and plays many roles during replication. This protein has an N-terminal domain (NTD) that has been shown to bind to several viral proteins, including UL11, VP22, and glycoprotein E, and these interactions are negatively regulated by a C-terminal domain (CTD). Thus, in pairwise transfections, UL16 binding is enabled only when the CTD is absent or altered. Based on these results, we hypothesized that direct interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 92 publications
(135 reference statements)
2
10
0
Order By: Relevance
“…Such ORFs were not found in S. plana, but a conserved domain was identified in the insertion, i.e. PHA03247 large tegument protein UL36, which is conserved among herpesviruses and plays many roles in viral replication [45]. Interestingly, this result is in line with a previous hypothesis that viral selfish elements may have colonized the male mitogenome in bivalves promoting its segregation into primordial germ cells and allowing its transmission to next generations [8,46].…”
Section: Discussionsupporting
confidence: 77%
“…Such ORFs were not found in S. plana, but a conserved domain was identified in the insertion, i.e. PHA03247 large tegument protein UL36, which is conserved among herpesviruses and plays many roles in viral replication [45]. Interestingly, this result is in line with a previous hypothesis that viral selfish elements may have colonized the male mitogenome in bivalves promoting its segregation into primordial germ cells and allowing its transmission to next generations [8,46].…”
Section: Discussionsupporting
confidence: 77%
“…Other studies have also suggested that VP22, which is encoded by the ul49 gene, is capable of interacting with cellular cGAS and inhibiting its enzymatic activity, as VP22 functions in the viral structural network . The tegument proteins encoded by ul16 and ul46 also show capacities to interact with cellular mitochondria and p85, growth factor receptor bound protein 2 (Grb2), and shc of the Src‐family kinases, respectively, as part of their roles in the viral structural network . These data describe a specific context for HSV infection, in which the viral strategy is to present only surface glycoproteins to the immune system, as most of the pathogenic viral molecules work within infected cells and can avoid monitoring by the innate and adaptive immune systems through various forms of immune evasion.…”
Section: The Structural Characteristics Of Hsv Determine Its Strategymentioning
confidence: 82%
“…Although the explanation for this unexpected phenotype remains to be elucidated, there are two properties of UL16 that raise the possibility that the innate cellular immune response might be enhanced when this viral protein is absent. First, UL16 has been shown to traffic to mitochondria during infection (70), and this is a known site for innate immune signaling (71). Second, in the absence of tegument protein UL37, packaging of UL16 into virions is reduced, suggesting a direct or indirect interaction between these two proteins.…”
Section: Discussionmentioning
confidence: 99%